Peripheral monocytes from Crohn’s disease patients retain functional responsiveness to GM-CSF during active disease - Winkel, Paul P.; Bergmann-Ewert, Wendy; Reiner, Johannes; Huth, Astrid; Kleimeier, Dana; Casalegno Garduño, Rosaely; Wrobel, Ida M.; Domanska, Grazyna; Däbritz, Jan; Wirthgen, Elisa (Frontiers in Immunology, 2025)
IntroductionCrohn’s disease (CD) is a relapsing inflammatory disease that is currently not curable. Despite the availability of anti-inflammatory treatments, 30–60% of patients develop resistance, necessitating the need for novel therapeutic approaches. Data from colitis models in mice indicate that granulocytemacrophage colony-stimulating factor (GM-CSF)-activated monocytes (GMaMs) may serve as a promising cellular therapy. However, it remains unclear whether inflammatory mediators, medication, or intrinsic defects impair the functionality of monocytes in active CD (aCD), potentially affecting their therapeutic efficacy.MethodsMonocytes from 8 aCD patients and healthy donors (HDs) were activated in vitro with GM-CSF, and their migratory capacity, adherence, metabolic activity, surface marker expression, and cytokine release were assessed. Cells were stimulated with lipopolysaccharides (LPS) to evaluate their inflammatory response.ResultsThe GMaM phenotype was characterized by increased metabolic activity, enhanced production of inflammatory cytokines, stronger adhesion, and remodeling of surface receptors involved in T-cell activation, compared to naïve monocytes. These features were largely comparable between aCD patients and HDs. LPS stimulation of GMaMs from both groups resulted in a significant production of pro-inflammatory and chemotactic cytokines, particularly interleukin (IL)-8 and monocyte chemotactic protein 1. Both are crucial recruiters of neutrophils and monocytes. Notably, monocytes from aCD patients showed an increased IL-10 response to GM-CSF, while the LPS-induced tumor necrosis factor-alpha and interferon-gamma release were reduced compared to HDs.DiscussionPeripheral monocytes from aCD patients retain functional responsiveness to GM-CSF activation, displaying preserved migratory, adhesive, metabolic, and cytokine responses. Differences in cytokine production by aCD monocytes may reflect disease-specific regulation, but do not appear to limit their suitability as cellular therapeutics.